Efficacy of emotion regulation techniques in hopelessness, worry, and anxiety in chronic infertile women: A short report - Ghahari, Shahrbanoo; Ghayoomi, Raoofeh; Babagolzadeh, Hajar; Khoshsekkeh, Mahnaz; Mohamadpour-Nikbin, Nilofar; Shams, Ghazaleh; Majidi, Nahid; Mazloumirad, Mohammad (Chronic Diseases Journal, 2022)
BACKGROUND: Infertility, as an important stressful factor, is involved in development of mood disorders. In this regard, this study assessed the effect of emotion regulation techniques on hopelessness, worry, and anxiety symptoms in chronic infertility in women. METHODS: This was a semi-experimental study with pretest-posttest design and control group. Statistical population consisted of infertile women who referred to gynecology clinics in Tehran, Iran, in 2017. All individuals fulfilled the anxiety and depression questionnaires and then, 30 women were selected randomly in two experimental and control groups, 15 persons in each group. Emotion regulation techniques were implemented on experimental group once a week, but the control group was on the waiting list. Both groups fulfilled the Beck Anxiety Inventory (BAI), Beck Hopelessness Scale (BHS), and the Penn State Worry Questionnaire (PSWQ) in baseline and the end of the intervention. The results were analyzed using multivariate analysis of variance (MANOVA) and SPSS software. RESULTS: Emotion regulation techniques led to reduction of worry (F(1,30) = 8.29, P < 0.05, d = 0.71), hopelessness (F(1,30) = 6.32, P < 0.01, d = 0.57), and anxiety (F(1,30) = 8.69, P < 0.05, d = 0.39) in infertile women. CONCLUSION: Considering the effectiveness of emotion regulation techniques in reduction of anxiety, hopelessness, and worry in infertile women, these techniques could be applied for improvement of mood in infertile women.